2011
DOI: 10.1111/j.1365-2699.2011.02565.x
|View full text |Cite
|
Sign up to set email alerts
|

Ephemeral Pleistocene woodlands connect the dots for highland rattlesnakes of the Crotalus intermedius group

Abstract: Aim  To test how Pleistocene climatic changes affected diversification of the Crotalus intermedius species complex. Location  Highlands of Mexico and the south‐western United States (Arizona). Methods  We synthesize the matrilineal genealogy based on 2406 base pairs of mitochondrial DNA sequences, fossil‐calibrated molecular dating, reconstruction of ancestral geographic ranges, and climate‐based modelling of species distributions to evaluate the history of female dispersion. Results  The presently fragmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 61 publications
6
58
1
Order By: Relevance
“…Bryson et al (2011a) concluded that major lineages in the C. triseriatus Group diverged through orogenic vicariance during the late Neogene, with most phylogeographic structuring within these major lineages attri butable to Quaternary glacialinterglacial climatic cycles. A similar pattern was recovered for the C. intermedius Group, although lineage formation was biased toward the Quaternary rather than the Neogene (Bryson et al 2011b). Because C. polystictus occurs at high elevations, but does not inhabit montane forests, it may have responded differently to Quaternary climatic events than have progenitors of the C. triseriatus and C. intermedius groups, the members of which primarily inhabit pine-oak forests.…”
Section: Introductionsupporting
confidence: 66%
“…Bryson et al (2011a) concluded that major lineages in the C. triseriatus Group diverged through orogenic vicariance during the late Neogene, with most phylogeographic structuring within these major lineages attri butable to Quaternary glacialinterglacial climatic cycles. A similar pattern was recovered for the C. intermedius Group, although lineage formation was biased toward the Quaternary rather than the Neogene (Bryson et al 2011b). Because C. polystictus occurs at high elevations, but does not inhabit montane forests, it may have responded differently to Quaternary climatic events than have progenitors of the C. triseriatus and C. intermedius groups, the members of which primarily inhabit pine-oak forests.…”
Section: Introductionsupporting
confidence: 66%
“…We used the species tree topology and associated multilocus-based branch lengths from Kubatko et al [22] as our estimate of the phylogeny for this group with the exception that we added C. atrox to the phylogeny. To estimate a value for the multilocus branch length connecting C. atrox with the Sistrurus ingroup clade, we used divergence estimates based on mtDNA ATP6–8 gene sequences from C. atrox [30] and S. miliarius and S. catenatus [22]. Venom composition for each taxa was measured as the relative percent of total venom composition made up by proteins from distinct families using data from this study and Sanz et al [23] for Sistrurus , Calvete et al [25] for C. atrox and Calvete et al [unpublished data – see Supplemental Information] for A. c. contortrix .…”
Section: Methodsmentioning
confidence: 99%
“…[22]. Branch lengths for C. atro x were estimated based on mtDNA ATP6–8 gene sequence divergences between C. atrox [30] and S. miliarius and S. catenatus [22].…”
Section: Introductionmentioning
confidence: 99%
“…In Arizona and northern mainland Mexico (Sonora), unsampled populations are predicted to occur in montane habitats between known Sitalcina catalina - Sitalcina rothi populations, and south of our current sample. We are not aware of Sitalcina records from northern mainland Mexico, but based on habitat and distribution of other regional sky-island animal taxa (e.g., Maddison and McMahon 2000, Bryson et al 2011, Bryson et al 2013, Grummer et al 2014), we expect Sitalcina to occur in the mountains of Sonora.…”
Section: Resultsmentioning
confidence: 99%
“…For many lineages, montane populations in southern Arizona constitute a “northern tip of a southern iceberg”, with centers of distribution found in northern Mexico (e.g., montane jumping spiders - Maddison and McMahon 2000, montane rattlesnakes - Bryson et al 2011). The desert canyons of southern California plus Baja California Norte constitute another distributional area with potentially high unknown diversity.…”
Section: Discussionmentioning
confidence: 99%